Breast Cancer–related Lymphedema in Valle del Cauca, Colombia: Prevalence, Risk Factors, and Characterization - María Isabel Cadena Ríos, MD, MSc; Jaume Masia, MD, PhD; Daniela Alvarez-Garcia, MD; Joan Sebastian Londoño Jimenez, MD; Juan Felipe Jimenez Trujillo, MD; Camilo Cardona Solano, MD; Raúl Devia-Rodríguez, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Breast cancer–related lymphedema (BCRL) significantly affects patients’ quality of life. Prevalence estimates in Latin America, particularly Colombia, remain inconsistent because of the limited research. This study aimed to determine the prevalence of BCRL and characterize its clinical and surgical aspects, as well as potential risk factors, in southwestern Colombia. Methods:. This multicenter case-control study included 334 women diagnosed with unilateral breast cancer between 1997 and 2019. The patients underwent standardized medical interviews, physical examinations, and data collection regarding clinical variables. Statistical analyses included descriptive statistics, bivariate logistic regression, and multivariable logistic regression to identify risk factors. Results:. The prevalence rate of BCRL was 23.9%. Patients with BCRL had a significantly higher body mass index and were more likely to have infiltrating ductal carcinoma. The surgical and treatment characteristics did not differ significantly between the groups. Multivariate analysis identified body mass index and arm swelling as risk factors for BCRL. Conclusions:. This study provides crucial data on the prevalence and risk factors of BCRL in Colombia, which will guide future research in developing a reproducible, easily accessible method for early lymphedema detection in remote populations. This, in turn, will enable timely referrals to centers equipped for proper management. Additionally, the findings can inform public policies aimed at preventing and improving the treatment of this complication.